A primazia do justo sobre o bem : as críticas de Rawls ao utilitarismo - Dalsotto, Lucas Mateus (My University, 2014)
The dissertation is to investigate claims specifically Rawlsian idea of the primacy of the right over the good, explaining, the basis of this concept, the critique of Rawls addressed to utilitarianism as a moral theory comprehensively. We seek to show that Rawls's assumption that utilitarianism is presented as a comprehensive moral theory which aims to present a general criterion (the principle of the greatest happiness, well- being, pleasure...) that applies to a broad spectrum issues (if not almost all issues). The Rawlsian view, in a society marked by a pluralism of comprehensive conceptions of the good, which, in most cases, have profound and irreconcilable differences, the utilitarian theory does not lend itself as a criterion for resolving moral dilemmas and political. It needs to find a set of principles capable of providing a common point of view from which it is possible to mediate contentious disputes arising from these different conceptions. In this case, the primacy of the right over the good in Rawls' theory has the sense that the principles of justice does not presuppose any particular conception of the good and that they put limits to the ways of life in which citizens can engage in conduct conceptions of the good they believe to be true.
A dissertação tem como pretensão investigar especificamente a ideia rawlsiana da primazia do justo sobre o bem, explicitando, a partir desse conceito, a crítica de Rawls dirigida ao utilitarismo enquanto uma teoria moral abrangente. Buscamos mostrar que o pressuposto de Rawls é de que o utilitarismo se apresenta como uma teoria moral abrangente que tem como finalidade apresentar um critério geral (o princípio da maior felicidade, bemestar, prazer...) que se aplica a um amplo espectro de questões (senão a quase todas as questões). Do ponto de vista rawlsiano, em uma sociedade marcada por um pluralismo de concepções abrangentes de bem, as quais, na maioria das vezes, têm divergências profundas e irreconciliáveis, a teoria utilitarista não se presta como critério para a resolução de impasses morais e políticos. É preciso encontrar um conjunto de princípios capaz de fornecer um ponto de vista comum a partir do qual seja possível mediar às controvérsias provenientes das disputas entre estas diversas concepções. Nesse caso, a primazia do justo sobre o bem na teoria de Rawls tem o sentido de que os princípios de justiça não pressupõem nenhuma concepção específica de bem e de que eles colocam os limites às formas de vida pelas quais os cidadãos podem se empenhar em realizar as concepções do bem que julgam ser verdadeiras.
Keywords: Rawls, John; Utilitarismo; Filosofia; Utilitarianism; Philosophy